2007
DOI: 10.1159/000108337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Speech Stimuli and Dysarthria Severity on Intelligibility Scores and Listener Confidence Ratings for Speakers with Cerebral Palsy

Abstract: This study examined differences among transcription intelligibility scores and listener confidence ratings for three different types of speech stimuli – single words, unrelated sentences, and sentences forming a narrative – all produced by speakers with dysarthria. Twelve speakers with dysarthria of varying severity secondary to cerebral palsy and 144 listeners participated in this study. Results showed that both intelligibility scores and confidence ratings were differentially affected by both stimuli and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 26 publications
9
65
3
Order By: Relevance
“…This contradicted findings reported in the literature that speech materials have differential effects on intelligibility of dysarthric speakers of different severity [25][26][27]. Although intelligibility ratings were carried out with different approaches in the above-mentioned studies (orthographic transcription) compared to our study, Yorkston and Beukelman pointed to a close approximation of the two measures [26].…”
Section: Discussioncontrasting
confidence: 99%
“…This contradicted findings reported in the literature that speech materials have differential effects on intelligibility of dysarthric speakers of different severity [25][26][27]. Although intelligibility ratings were carried out with different approaches in the above-mentioned studies (orthographic transcription) compared to our study, Yorkston and Beukelman pointed to a close approximation of the two measures [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Externally cued tasks, by their very nature, often heighten a person's awareness and attention to the task. In fact, environmental factors such as use of speech materials and the physical setting have been shown to increase typical speakers' attention to their speech production, enhancing performance (Goberman & Elmer, 2005;Hustad, 2007;Kent, Weismer, Kent, & Rosenbek, 1989). The same improvements have been found in individuals with PD (Keintz et al, 2007;Neely, 1956;Sarno, 1968;Weismer, 1984).…”
Section: Perceptual Ratings Of Naturalnessmentioning
confidence: 86%
“…Judgments of intelligibility of speech can be influenced by several factors (1) related to the listener (3)(4)(5)(6)(7)(8)(9)(10)(11) , the speaker (4,5,(7)(8)(9) or even the assessment instrument (1,(3)(4)(5)8,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . With regard to assessment instruments, one such influencing factor is stimulus type (8) .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to assessment instruments, one such influencing factor is stimulus type (8) . Many studies have identified the effect of using different speech stimuli on intelligibility scores (4,5,8,(12)(13)(14)(15)17,18,(23)(24)(25)(26) . Some of these studies have shown that the greater the number of semantic cues available to listeners, the higher the intelligibility scores of speakers (4,8,17,18,24) .…”
Section: Introductionmentioning
confidence: 99%